ÍNDICE DE CONFIANÇA DO EMPRESÁRIO VAREJISTA DE SANTA ROSA EM MARÇO DE 2009 - Graef, Nelinho D.; Zamberlan, Luciano; Sparemberger, Ariosto; Büttenbender, Pedro L.; Mallmann, Carla; Hofler, Claudio (Salão do Conhecimento, 2013)
Resumo